Bankruptcy Prediction and Financial Risk Analysis of PT AIA Financial and PT Allianz Life Insurance Indonesia Using The Altman Z-Score Model - Fitrasia, Muthia; Pasha, Raisa (iora, 2025)
This study analyzes and compares the bankruptcy risk of PT AIA Financial and PT Asuransi Allianz Life Indonesia using the Altman Z-Score model based on financial reports for the period 2018–2024. The results show that both companies are in the grey zone, indicating potential financial risk even though they have not actually gone bankrupt. PT Allianz was in the distress zone in 2018 before improving, while PT AIA showed better stability with an upward trend in Z-Score in recent years. The Altman Z-Score model has proven to be effective as an early warning system for monitoring the financial health of insurance companies and supporting decision-making in risk mitigation.